Can reducing black carbon and methane below RCP2.6 levels keep global warming below 1.5 °C?. (25th April 2018) - Jones, Andy; Haywood, James M.; Jones, Chris D.
Abstract : Methane and black carbon aerosols have been identified as exerting the two strongest positive radiative forcings after carbon dioxide and therefore drastic reductions in these atmospheric constituents could potentially offer strong leverage in reducing global warming. Using the HadGEM2‐ES model, we reduce concentrations of methane and black carbon while holding all other emissions at representative concentration pathway RCP2.6 levels to examine whether we can achieve the target of keeping global‐mean temperature rise below 1.5 °C relative to the pre‐industrial level during the remainder of the 21st century. We find that even total cessation of black carbon aerosol emissions is ineffective in attaining this goal. Reducing methane concentrations at four times the rate assumed in RCP2.6 is able to return warming levels to below 1.5 °C by the 2070s but overshoots the target level prior to that. As RCP2.6 represents an optimistic scenario relative to the Intended Nationally Determined Contributions, our results highlight the importance of deep and rapid reductions in both CO2 and methane emissions if humanity is serious about attaining the 1.5 °C target. Abstract : Even the most optimistic climate change scenarios struggle to meet the aspirational 1.5 °C target of the Paris climate agreement. Here we examine the contributions of even further reductions in black carbon aerosols or methane concentrations. We find little effect from black carbon removal and that methane must be reduced at four times the rate currently considered to have an impact, emphasizing the need for deep and rapid reductions in carbon dioxide emissions.